Socialization and Community Awareness in Preventing COVID-19 Through Social Media by Implementing Faith, Immunization, and Safety in the Community of Sukmajaya Subdistrict, Cilegon City - Ima Maisaroh; Muhammad Ananda Musaly; Rizky Haidiana Sri Barkah; Riska Putri Damayanti; Inzaghi Fakhri Alfarisi; Anisa Tiara Wahyuni; Cylvi Claudia Syafitri; Anisa Puspitasari (MOVE: Journal of Community Service and Engagement, 2023)
Applying clean and healthy behavior (PHBS) is important to implement in life, especially during a pandemic like what the whole world is currently experiencing. The importance of maintaining this is also inseparable from maintaining faith and immunity that we must always keep. The purpose of this activity is to educate and utilize the available time to increase the knowledge and faith of residents around Sukmajaya Subdistrict. By using online socialization methods through the creation of several video content such as educational videos on the prevention of COVID-19 transmission, distribution of hand sanitizers, medical masks, pamphlets, leaflets, and several webinars including religious, health, and entrepreneurship topics. Such as how our behavior can prevent the spread of the COVID-19 virus in the community, how to use leisure time to continue to get closer to the Almighty, and how we can survive during the pandemic with all efforts, especially entrepreneurship, by holding activities that open up more opportunities for MSME entrepreneurs for residents of Sukmajaya Subdistrict, Jombang District, Cilegon City.